The T alpha 2 nuclear protein binding site from the human T cell receptor alpha enhancer functions as both a T cell-specific transcriptional activator and repressor (The Rockefeller University Press, 1990)
T cell-specific expression of the human T cell receptor alpha (TCR- alpha) gene is regulated by the interaction of variable region promoter elements with a transcriptional enhancer that is located 4.5 kb 3' of the TCR-alpha constant region (C alpha) gene segment. The minimal TCR- alpha enhancer is composed of two nuclear protein binding sites, T alpha 1 and T alpha 2, that are both required for the T cell-specific activity of the enhancer. The T alpha 1 binding site contains a consensus cAMP response element (CRE), and binds a set of ubiquitous nuclear proteins. The T alpha 2 binding site does not contain known transcriptional enhancer motifs. However, it binds at least two nuclear protein complexes, one of which is T cell specific. We now report that although the T alpha 2 nuclear protein binding site displays transcriptional activator activity in the context of the TCR-alpha enhancer, this site alone can function as a potent, T cell-specific transcriptional repressor when positioned either upstream, or downstream of several heterologous promoter and enhancer elements. These results demonstrate that a single nuclear protein binding site can function as a T cell-specific transcriptional activator or repressor element, depending upon the context in which it is located.